Magnetic resonance imaging features of parotid mucoepidermoid carcinoma: a retrospective analysis - Ravishankar, Dev; Sunil, Devika (International Surgery Journal, 2023)
Background: Parotid mucoepidermoid carcinoma (P-MEC) is the most common of malignant salivary gland tumors and its accurate preoperative diagnosis is crucial for better management and prognostication. This becomes even more critical because in most cases P-MEC is difficult to distinguish from other common benign parotid lesions including abscess both clinically and radiologicall, but where management is entirely different. MRI could prove a vital cog in the wheel in this whole endeavor. This study aims to analyse the various MRI features in parotid mucoepidermoid carcinoma and the control group of non-MEC benign parotid masses which will aid in better distinguish between the two entities thereby coming to a confident diagnosis which will aid in management planning and better prognosis. Methods: This retrospective study was conducted at Sree Uthradom Thirunal Academy of Medical Science (SUTAMS), Thiruvananthapuram, India from July 2021 to July 2022 after obtaining Institutional Ethical committee approval. An informed consent was obtained from all patients before conduct of MRI imaging. The various MRI findings was applied in 60 patients in age bracket of 45-90 yrs with HPE proven parotid gland tumors. The cohort was divided into 2 groups: MEC (n=30) and non–MEC (n=30) as a control group. Results: Logistic regression analysis identified presence of cystic component (p<0.001), T1 hypointense signal (p<0.001), T2 hyperintense signal (p<0.001), heterogeneous post contrast enhancement (p<0.001) and perineural invasion (p=0.002) as characteristic MRI features of parotid MEC that aided in its accurate distinction from other non-MEC lesions of parotid. Conclusions: MRI can be a valuable tool for reliably distinguishing parotid mucoepidermoid from other parotid lesions.